Activity of Skin Secretions of Frog Fejervarya limnocharis and Limnonectes macrodon against Streptococcus pneumoniae Multidrug Resistant and Molecular Analysis of Species F. limnocharis - Jajang Suhyana; I Made Artika; Dodi Safari (Current Biochemistry, 2015)
Indonesia has about 450 frog species which is approximately 20% of frog species in the world. Among frog species found in Indonesia are Fejervarya limnocharis dan Limnonectes macrodon belonging to family Dicroglossidae. Frog skin secretion is considered to have a potency to be used as an alternative source of antibacterial agent against Streptococcus pneumoniae multidrug resistant (MDR). The aims of the present study were to analyze antibacterial activity of skin secretions of F. limnocharis and L. macrodon against S. pneumoniae multidrug resistant (MDR) and conduct molecular phylogenetic analysis of the frog used to ensure classification of frog species. The release of skin secretion was stimulated using epinephrine injection. Antibacterial activity of the skin secretions was tested using the well and paper disc methods. Results showed that skin secretions of F. limnocharis have antibacterial activity against S. pneumoniae multidrug resistant (MDR) SPN1307. The activity, however, was lower compared to that of chloramphenicol in both well and paper disc methods. On the other hand, skin secretions of L. macrodon failed to inhibit the growth of S. pneumoniae multidrug resistant (MDR) SPN1307. Molecular phylogenetic analysis was carried out on F. limnocharis based on DNA sequence of a partial fragment of mitochondrial cytochrome oxidase subunit I (COI) gene. Results showed that the frog F. limnocharis is closely related (97%) to Fejervarya sp from Bali. Skin secretions of F. limnocharis, therefore, has the potency to be developed as a source of antibacterial agents against S. pneumoniae multidrug resistant (MDR) SPN1307.